O MARKETING PESSOAL E SUA IMPORTÂNCIA PARA OS GESTORES DO SETOR VAREJISTA DO MUNICÍPIO DE SANTA ROSA - Graef, Nelinho D.; Zamberlan, Luciano; Oliveira, Charlene; Martini, Rodrigo N.; Wagner, Wander G.; Martinelli, Marlen; Sparemberger, Ariosto; Büttenbender, Pedro L. (Salão do Conhecimento, 2013)
Resumo